Nurse knowledge about potentially inappropriate medications for elderly - Garcia Soares, Gabriela (2021)
Due to the consequences of changes in fertility and mortality rates, there is an increase in population aging. In this context, the use of potentially inappropriate medications in this population makes nurses important agents in the identification of adverse reactions, requiring their knowledge about these drugs and their effects. The study aimed to verify nurses knowledge about the 2015 AGS BeersCriteria, regarding the potentially inappropriate medications for the elderly, and their adverse effects. It is a cross-sectional, descriptive, and analytical study with a quantitative and qualitative approach performed in a teaching hospital in the Triângulo Mineiro, Minas Gerais. Of the 80 professionals, 74.1% reported attending the elderly frequently, and only 3.8% had a specialization course in elderly health. Only 13.8% reported knowing the Beers Criteria. And 69% believe that adverse drug reactions can be confused as a new symptom and because of this, new drugs can be inserted into the therapeutic plan. Three categories emerged: The importance of assertive knowledge about PIMs, The nurse as a fundamental character in ADR, and Knowledge as a reinforcer of care. There is evidence of the need to train nurses to better identify adverse drug reactions so that they can act on these events avoiding the worsening of the individual.